Mutual Interactions of Silymarin and Colon Microbiota in Healthy Young and Healthy Elder Subjects - Tomisova, Katerina; Jarosova, Veronika; Marsik, Petr; Bergo, Anna Mascellani; Cinek, Ondrej; Hlinakova, Lucie; Kloucek, Pavel; Janousek, Vaclav; Valentová, Kateřina; Havlik, Jaroslav (Molecular nutrition & food research, 2024)
SCOPE: This multi-omic study investigates the bidirectional interactions between gut microbiota and silymarin metabolism, highlighting the differential effects across various age groups. Silymarin, the extract from Silybum marianum (milk thistle), is commonly used for its hepatoprotective effects. METHODS AND RESULTS: An in vitro fermentation colon model was used with microbiota from 20 stool samples obtained from healthy donors divided into two age groups. A combination of three analytical advanced techniques, namely proton nuclear magnetic resonance (1H NMR), next-generation sequencing (NGS), and liquid chromatography-mass spectrometry (LC-MS) was used to determine silymarin microbial metabolites over 24 h, overall metabolome, and microbiota composition. Silymarin at a low diet-relevant dose of 50 μg mL-1 significantly altered gut microbiota metabolism, reducing short-chain fatty acid (acetate, butyrate, propionate) production, glucose utilization, and increasing alpha-diversity. Notably, the study reveals age-related differences in silymarin catabolism. Healthy elderly donors (70-80 years) exhibited a significant increase in a specific catabolite associated with Oscillibacter sp., whereas healthy young donors (12-45 years) showed a faster breakdown of silymarin components, particularly isosilybin B, which is associated with higher abundance of Faecalibacterium and Erysipelotrichaceae UCG-003. CONCLUSION: This study provides insights into microbiome functionality in metabolizing dietary flavonolignans, highlighting implications for age-specific nutritional strategies, and advancing our understanding of dietary (poly)phenol metabolism.
Keywords: senioři; Feces; senioři nad 80 let; střevní mikroflóra; Healthy Volunteers; mladiství; Middle Aged; kyseliny mastné těkavé; mužské pohlaví; silymarin; Adult; mladý dospělý; Gastrointestinal Microbiome; dítě; Silymarin; Child; Colon; Aged, 80 and over; Young Adult; ženské pohlaví; Fatty Acids, Volatile; feces; Humans; kolon; fermentace; lidé středního věku; Fermentation; dospělí; Female; Aged; Adolescent; lidé; Male; zdraví dobrovolníci pro lékařské studie